2021
DOI: 10.3389/fsurg.2020.587921
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anterior Inferior Iliac Spine Dysmorphism and Development of a Novel Classification System: An Anatomic Study of 1,797 Cadaveric Specimens

Abstract: Purpose: Subspine impingement occurs due to a morphologically abnormal anterior inferior iliac spine (AIIS), capable of causing impingement against the distal femoral neck. The purpose of this investigation was to determine the prevalence of AIIS dysmorphism based on specimen sex, race, and age, while introducing a novel anatomic-based classification system.Methods: A total of 1,797 adult cadaveric specimens (n = 3,594 hemipelvises) were analyzed. AIIS with the potential for subspine impingement (SSI) was reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recent anatomic data based on 1797 cadaveric specimens reported that AIIS dysmorphism was present in 6.4%. 20 This is lower than the current rate for patients undergoing hip arthroscopy.…”
Section: Discussionmentioning
confidence: 81%
“…Recent anatomic data based on 1797 cadaveric specimens reported that AIIS dysmorphism was present in 6.4%. 20 This is lower than the current rate for patients undergoing hip arthroscopy.…”
Section: Discussionmentioning
confidence: 81%